Characterization of Plasmodium relictum, a cosmopolitan agent of avian malaria - Gediminas Valkiūnas; Mikas Ilgūnas; Dovilė Bukauskaitė; Karin Fragner; Herbert Weissenböck; Carter T. Atkinson; Tatjana A. Iezhova (Malaria Journal, 2018)
Abstract Background Microscopic research has shown that Plasmodium relictum is the most common agent of avian malaria. Recent molecular studies confirmed this conclusion and identified several mtDNA lineages, suggesting the existence of significant intra-species genetic variation or cryptic speciation. Most identified lineages have a broad range of hosts and geographical distribution. Here, a rare new lineage of P. relictum was reported and information about biological characters of different lineages of this pathogen was reviewed, suggesting issues for future research. Methods The new lineage pPHCOL01 was detected in Common chiffchaff Phylloscopus collybita, and the parasite was passaged in domestic canaries Serinus canaria. Organs of infected birds were examined using histology and chromogenic in situ hybridization methods. Culex quinquefasciatus mosquitoes, Zebra finch Taeniopygia guttata, Budgerigar Melopsittacus undulatus and European goldfinch Carduelis carduelis were exposed experimentally. Both Bayesian and Maximum Likelihood analyses identified the same phylogenetic relationships among different, closely-related lineages pSGS1, pGRW4, pGRW11, pLZFUS01, pPHCOL01 of P. relictum. Morphology of their blood stages was compared using fixed and stained blood smears, and biological properties of these parasites were reviewed. Results Common canary and European goldfinch were susceptible to the parasite pPHCOL01, and had markedly variable individual prepatent periods and light transient parasitaemia. Exo-erythrocytic and sporogonic stages were not seen. The Zebra finch and Budgerigar were resistant. Neither blood stages nor vector stages of all examined P. relictum lineages can be distinguished morphologically. Conclusion Within the huge spectrum of vertebrate hosts, mosquito vectors, and ecological conditions, different lineages of P. relictum exhibit indistinguishable, markedly variable morphological forms. Parasites of same lineages often develop differently in different bird species. Even more, the variation of biological properties (parasitaemia dynamics, blood pathology, prepatent period) in different isolates of the same lineage might be greater than the variation in different lineages during development in the same species of birds, indicating negligible taxonomic value of such features. Available lineage information is excellent for parasite diagnostics, but is limited in predictions about relationships in certain host-parasite associations. A combination of experiments, field observations, microscopic and molecular diagnostics is essential for understanding the role of different P. relictum lineages in bird health.